Pemberdayaan Anak Panti Asuhan Melalui Pelatihan Kerajinan Manik- Manik Dan Pemasaran Syariah Di Panti Asuhan Asrama Sahabat Yatim Makassar - Muh. Rohman; Ferdinan; Ahista Maharani; Nurahmi Ramadhani; Aulia Agustina; Annisa Syahratul Jannah; Rohani; Samsunandar; Fanny Fitri Fadillah; Feri; Mawar; Armayanti; Andi Muhammad Taufiq; Muhammad Raihandi; Riska Amelia; Ranti; M. Mubdi Fahril; Ummu Kalsum; Rian Muhammad Reski; Asdar; Nasrullah; Muhammad Akbar Kadir; Andi Alif Rifai Ukkas; Aswandi Sadril; Fajar Eko Purnama Rustan; Dimas Dwi Raharjo; Muh. Asrullah Muslim; Alfarah Firdayanti; Ayulia; Lilis Istiyani (CV. ITTC INDONESIA, 2025)
This community service activity was carried out at the Sahabat Yatim Orphanage in Makassar, aiming to empower orphanage children through handicraft training and sharia-based marketing education. The method used includes preparation, implementation, and evaluation stages. The children were taught to create bead crafts such as bracelets and keychains, and were also introduced to Islamic marketing principles such as honesty and fairness. The results showed an increase in participants’ entrepreneurial skills and understanding, as well as successful product sales through direct practice. Additionally, social assistance was provided, and a strong emotional bond was established between the organizers and the children. This activity serves as a real example of how practical training combined with Islamic values can promote self-reliance among orphaned children.